REVIEW OF NUMERICAL SCHEMES AND BOUNDARY CONDITIONS APPLIED TO WAVE PROPAGATION PROBLEMS - Almeida, Odenir de (Revista de Engenharia Térmica, 2016)
As a review framework, the present study describes the application and performance of different numerical schemes for Computational Aeroacoustics (CAA) of simple wave propagation problems. The current approach aims to simulate pulse propagation on the near field by the use of different spatial and temporal numerical schemes for the full and Linearized Euler Equations (LEE) in a dimensional and dimensionless formulation. Comparisons of processing time, residual error and quality of results are present and discussed shedding light to the relevant parameters which play important role in aeroacoustics. The investigation is focused on different Gaussian pulse propagation cases in unbounded and bounded domains which is solved by using optimized spatial and temporal schemes for reducing dissipative and dispersive errors. The numerical results are compared with the exact analytical solutions when available, showing good agreement.